2015
DOI: 10.3201/eid2108.141336
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Patterns of Buruli Ulcer Incidence, Central Africa, 2002–2012

Abstract: To determine when risk for Buruli ulcer is highest, we examined seasonal patterns in a highly disease-endemic area of Cameroon during 2002–2012. Cases peaked in March, suggesting that risk is highest during the high rainy season. During and after this season, populations should increase protective behaviors, and case detection efforts should be intensified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 12 publications
(19 reference statements)
0
27
0
Order By: Relevance
“…In Central Africa, it was shown that cases of Buruli ulcer peaked in March, suggesting that the risk is highest during the rainy season (377). In Cameroon, in the Nyong River distance model, the risk of Buruli ulcer decreased when the distance to the river increased, with a dose-response relationship (378).…”
Section: Geography Of Buruli Ulcermentioning
confidence: 99%
See 1 more Smart Citation
“…In Central Africa, it was shown that cases of Buruli ulcer peaked in March, suggesting that the risk is highest during the rainy season (377). In Cameroon, in the Nyong River distance model, the risk of Buruli ulcer decreased when the distance to the river increased, with a dose-response relationship (378).…”
Section: Geography Of Buruli Ulcermentioning
confidence: 99%
“…In Japan, it was proven that there is a dynamic seasonal appearance of M. ulcerans in the environment, which may contribute to the seasonal variation of Buruli ulcer occurrence (108). In Central Africa, it was shown that the cases of Buruli ulcer peaked in March, suggesting that the risk is at its highest during the rainy season (377). In each country of endemicity, there is a distinct geographical distribution, depending on environmental factors.…”
Section: Geography Of Buruli Ulcermentioning
confidence: 99%
“…The disease occurs in very concentrated, small geographic foci within countries, as described in Cameroon and Australia (16,17). Increases in cases have been associated with heavy periods of rainfall in some places (18)(19)(20)(21). In Africa, landscape fragmentation and destruction has been suggested as a risk factor for Buruli ulcer (22).…”
mentioning
confidence: 99%
“…10, 59 As discussed here, the interplay between deforestation (changes in landscape ecology and topography) and rainfall events (flooding) allow the redistribution of MU in new environments where abiotic and biotic conditions enhance its prevalence and increase contact rates with human hosts. In addition, at the start of the dry season, these lentic habitats become more accessible for a whole range of human activities, such as crab hunting, fishing, bathing and washing clothes.…”
Section: Introductionmentioning
confidence: 98%